Lycopene Metabolite, Apo-10′-Lycopenoic Acid, Inhibits Diethylnitrosamine-Initiated, High Fat Diet–Promoted Hepatic Inflammation and Tumorigenesis in Mice - Blanche C. Ip; Kang‐Quan Hu; Chun Liu; Donald E. Smith; Martin S. Obin; Lynne M. Ausman; Xiangdong Wang (2013)
Obesity is associated with increased risk in hepatocellular carcinoma (HCC) development and mortality. An important disease control strategy is the prevention of obesity-related hepatic inflammation and tumorigenesis by dietary means. Here, we report that apo-10'-lycopenoic acid (APO10LA), a cleavage metabolite of lycopene at its 9',10'-double bond by carotene-9',10'-oxygenase, functions as an effective chemopreventative agent against hepatic tumorigenesis and inflammation. APO10LA treatment on human liver THLE-2 and HuH7 cells dose dependently inhibited cell growth and upregulated sirtuin 1 (SIRT1), a NAD(+)-dependent protein deacetylase that may suppress hepatic carcinogenesis. This observed SIRT1 induction was associated with decreased cyclin D1 protein, increased cyclin-dependent kinase inhibitor p21 protein expression, and induced apoptosis. APO10LA supplementation (10 mg/kg diet) for 24 weeks significantly reduced diethylnitrosamine-initiated, high fat diet (HFD)-promoted hepatic tumorigenesis (50% reduction in tumor multiplicity; 65% in volume) and lung tumor incidence (85% reduction) in C57Bl/6J mice. The chemopreventative effects of APO10LA were associated with increased hepatic SIRT1 protein and deacetylation of SIRT1 targets, as well as with decreased caspase-1 activation and SIRT1 protein cleavage. APO10LA supplementation in diet improved glucose intolerance and reduced hepatic inflammation [decreased inflammatory foci, TNFα, interleukin (IL)-6, NF-κB p65 protein expression, and STAT3 activation] in HFD-fed mice. Furthermore, APO10LA suppressed Akt activation, cyclin D1 gene, and protein expression and promoted PARP protein cleavage in transformed cells within liver tumors. Taken together, these data indicate that APO10LA can effectively inhibit HFD-promoted hepatic tumorigenesis by stimulating SIRT1 signaling while reducing hepatic inflammation.